Why storytelling is the future of branding - Pires, Sandra dos Santos (2017)
This thesis will show how storytelling is important to brands in the current days when so many companies sell similar products. This statement will be proven by an intensive research which will consist in the quoting of a lot of authors that studied the storytelling concept. It will also be presented many branding concepts such as: brand equity, brand image, brand personality, brand architecture, brand loyalty, emotional branding, the elements of a brand and, the process of creativity and the strategy behind it. Furthermore, this thesis will prove if indeed storytelling is a successful and important tool for brands to prosper in today’s business. This will be proved not only in a theoretical way but also, and more importantly, in a pratical way (this paper’s research question). To demonstrate the points above, a theoretical background will be presented first and then, a research method and its results will allow us to draw conclusions and answer this thesis’ research question.